ChatGPT in cardiovascular medicine: revolution, hype, or helper? - Uchmanowicz, Izabella; Jędrzejczyk, Maria; Vellone, Ercole; Janczak, Sara; Mirkowski, Karol; Uchmanowicz, Bartosz M.; Czapla, Michał (Frontiers in Public Health, 2025)
The integration of artificial intelligence (AI) into healthcare has opened new frontiers in clinical research and practice, particularly in data-rich disciplines like cardiovascular medicine. Among recent advancements, ChatGPT—a large language model developed by OpenAI—has garnered increasing attention for its potential to streamline workflows, support literature synthesis, and facilitate data interpretation. This review examines the multifaceted applications of ChatGPT in cardiovascular medicine, including its use in hypothesis generation, research design, evidence-based decision-making, and patient communication. ChatGPT offers the ability to process and summarize large volumes of medical literature and patient data, potentially enhancing the efficiency and accessibility of research activities. It can also assist in creating patient-friendly educational materials and support patient-centered care through more personalized communication. However, the use of generative AI models in clinical research raises critical concerns related to the accuracy of generated content, ethical implications, and the absence of contextual clinical judgment. Limitations such as hallucinations, data privacy issues, and the risk of overreliance on non-human decision-making must be addressed through rigorous oversight, validation, and clear guidelines for responsible use. While not a substitute for human expertise, ChatGPT can act as a valuable complementary tool that enhances research productivity and innovation in cardiovascular medicine. By supporting clinicians and researchers in navigating complex datasets and rapidly evolving evidence, ChatGPT holds promise as a facilitator of more efficient, inclusive, and responsive cardiovascular care—provided its integration is approached with caution and critical appraisal.